Prevention of surgical adhesions with gelatine sealing sheet in a canine adhesion model. (7th January 2022) - Niwa, Kosuke; Yamashita, Keigo; Hirose, Tomoaki; Hiraga, Shun; Fukuba, Ryohei; Takemura, Junichi; Nishikawa, Hiroshi; Taniguchi, Shigeki
Abstract: OBJECTIVES: Although reoperation has been increasingly performed in cardiovascular surgery in recent years, preventing surgical adhesions remains an unsolved complication. Therefore, this study aimed to investigate whether gelatine sealing sheets are more effective than fibrin sealing sheets in preventing surgical adhesions. METHODS: Bilateral femoral arteries of 20 beagle dogs under general anaesthesia were pricked with syringe needles, and gelatine and fibrin sealing sheets were applied on the bleeding points to make canine adhesion models. The femoral artery was harvested after 4 and 12 weeks to evaluate adhesion formations. The adhesive grade was quantified by scoring the area and strength of adhesion tissues. Histological staining was performed to examine the structural features of surgical adhesions. RESULTS: Significantly fewer macroscopic adhesions were observed with gelatine sealing sheets than those with fibrin sealing sheets at 4 and 12 weeks postoperatively. Microscopically, CD3+ T lymphocytes at 4 and 12 weeks postoperatively in gelatine sealing sheets were significantly lower than those in fibrin sealing sheets. Microvessel density determined by CD34 at 4 and 12 weeks postoperatively in gelatine sealing sheets was also significantly lower than those in fibrin sealing sheets. CONCLUSIONS: The gelatine sealing sheets are more effective than the fibrin sealing sheets in preventing surgical adhesions. These findings suggest that the gelatine sealing sheet may help prevent adhesions and thus be a therapeutically effective biomaterial in vascular surgery. Abstract : With ageing patients and increasing performance of cardiovascular surgeries, the number of reoperations has also been increasing [1–3].